Ethnicity-stratified analysis of the association between XRCC3 Thr241Met polymorphism and leukemia: an updated meta-analysis - Zhengjun Xie; Wei Peng; Qiuhua Li; Wei Cheng; Xin Zhao (BMC, 2021)
Abstract Background Presently, whether X-ray repair cross complementing group 3 (XRCC3) Thr241Met polymorphism is correlated to leukemia risk remains controversial. Because of this reason, the objective of current study is to explore whether XRCC3 Thr241Met polymorphism confers risk to leukemia. Methods Two independent authors systematically and comprehensively searched Pubmed, Embase, the Cochrane library, Google academic, China National Knowledge Infrastructure (CNKI). Search time is from database foundation to March 2021. Results Overall, significant associations between leukemia risk and XRCC3 Thr241Met polymorphism were found in Caucasian population by allele contrast (T vs. C: OR 1.20, 95% CI 1.02-1.40), homozygote comparison (TT vs. CC: OR 1.35, 95% CI 1.05-1.73), and recessive genetic model (TT vs. TC/CC: OR 1.31, 95% CI 1.04-1.64). Conclusions The present meta-analysis suggests that the XRCC3 Thr241Met polymorphism may be a risk factor for leukemia in Caucasian population.